Ancaman Budaya Pop (Pop Culture) Terhadap Penguatan Identitas Nasional Masyarakat Urban - Istiqomah, Annisa (JPW (Jurnal Politik Walisongo), 2020)
National identity is an understanding of people's identity in an entity that has a common destiny and purpose. National identity is understood as a dynamic condition that is formed due to ethnicity, territorial, linguistic and religious factors. One of the factors that influence the dynamics of national identity is globalization. Globalization is interpreted as the freedom of the world community to develop various aspects of life such as science, technology, values, and culture. The increasingly easy interaction of the global community has an impact on the process of transmitting cultural values across countries such as the development of pop culture in Indonesia. Based on the study of literature by the author, the development of pop culture can have a negative impact on strengthening national identity, especially among urban communities, especially at the age of adolescence. The negative impact of culture is westernized behavior which tends to be pragmatic, hedonistic, and consumptive. Such behavior is certainly very contrary to the ideology of Pancasila so that it becomes a threat to the Indonesian people in strengthening national identity based on Pancasila. Thus, efforts are needed to strengthen the national identity of urban communities especially teenagers through internalization of community cultural values (local wisdom) in various fields of life, filtering of foreign cultures, and multicultural education to strengthen the foundations of each individual so that they are not easily uprooted by their cultural roots